The contradictory role of androgens in cutaneous and major burn wound healing. Issue 1 (20th April 2021) - Shi, Huaikai; Cheer, Kenny; Simanainen, Ulla; Lesmana, Brian; Ma, Duncan; Hew, Jonathan J; Parungao, Roxanne J; Li, Zhe; Cooper, Mark S; Handelsman, David J; Maitz, Peter K; Wang, Yiwei
Abstract: Wound healing is a complex process involving four overlapping phases: haemostasis, inflammation, cell recruitment and matrix remodeling. In mouse models, surgical, pharmacological and genetic approaches targeting androgen actions in skin have shown that androgens increase interleukin-6 and tumor necrosis factor-α production and reduce wound re-epithelization and matrix deposition, retarding cutaneous wound healing. Similarly, clinical studies have shown that cutaneous wound healing is slower in men compared to women. However, in major burn injury, which triggers not only local wound-healing processes but also systemic hypermetabolism, the role of androgens is poorly understood. Recent studies have claimed that a synthetic androgen, oxandrolone, increases protein synthesis, improves lean body mass and shortens length of hospital stay. However, the possible mechanisms by which oxandrolone regulates major burn injury have not been reported. In this review, we summarize the current findings on the roles of androgens in cutaneous and major burn wound healing, as well as androgens as a potential therapeutic treatment option for patients with major burn injuries.